A field-expedient arm care screening tool can identify musculoskeletal risk factors in baseball players - Matsel, K. A.; Hoch, M. C.; Butler, R. J.; Westgate, P. M.; Malone, T. R.; Uhl, T. L. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Preseason movement screening can identify modifiable risk factors, deterioration of function, and potential for injury in baseball players. Limited resources and time prevent high school baseball coaches from performing movement screens on their players.